1990
DOI: 10.1177/073953298901100106
|View full text |Cite
|
Sign up to set email alerts
|

Gender Representation in Newspaper Business Sections

Abstract: Women in that traditional male bastion, the newspaper business section, are underrepresented as sources and subjects of stories, even when the business staff writers or editors are women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Over the past 40 years, a host of media studies have examined women’s representation in the press (Armstrong 2004; Jolliffe 1989; Kahn and Goldenberg 1991; Len-Rios et al 2005; Rodgers and Thorson 2003; Zoch and Turk 1998). These studies make different breadth versus depth trade-offs: Some work examines all pages of a single newspaper over a period of time (Davis 1982; Gallagher 2005, 2010; Len-Rios et al 2005; Spears and Seydegart 2000); other research focuses on the front pages of a larger number of sources over a longer period of time (Gibbons 2000; Potter 1985; Zoch and Turk 1998); and some studies focus on news photographs (Blackwood 1983; Miller 1975; Rodgers and Thorson 2000), the business section (Greenwald 1990), or the sports section (Duncan et al 1991; Huggins 1997). The findings of these studies are consistent: They all report substantial underrepresentation of female names, and they typically find that female names constitute approximately one fourth of all mentions.…”
Section: Empirical Research On Women’s Newspaper Coverage: a Persistementioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 40 years, a host of media studies have examined women’s representation in the press (Armstrong 2004; Jolliffe 1989; Kahn and Goldenberg 1991; Len-Rios et al 2005; Rodgers and Thorson 2003; Zoch and Turk 1998). These studies make different breadth versus depth trade-offs: Some work examines all pages of a single newspaper over a period of time (Davis 1982; Gallagher 2005, 2010; Len-Rios et al 2005; Spears and Seydegart 2000); other research focuses on the front pages of a larger number of sources over a longer period of time (Gibbons 2000; Potter 1985; Zoch and Turk 1998); and some studies focus on news photographs (Blackwood 1983; Miller 1975; Rodgers and Thorson 2000), the business section (Greenwald 1990), or the sports section (Duncan et al 1991; Huggins 1997). The findings of these studies are consistent: They all report substantial underrepresentation of female names, and they typically find that female names constitute approximately one fourth of all mentions.…”
Section: Empirical Research On Women’s Newspaper Coverage: a Persistementioning
confidence: 99%
“…Women are substantially underrepresented in the media in general and in the written press in particular (Davis 1982; Duncan, Messner, and Williams 1991; Greenwald 1990; Potter 1985; Zoch and Turk 1998). Scholars argue that the differential media coverage of women and men is not merely a reflection of existing gender inequities in economic participation, but rather that media practices exacerbate and artificially magnify these inequalities (De Swert and Hooghe 2010; Gallagher 2010; Tuchman 1978; Zoch and Turk 1998).…”
mentioning
confidence: 99%
“…Over the last 40 years, a host of media studies have examined women's representation in the press (Armstrong, ; Jolliffee, ; Kahn and Goldenberg, ; Len‐Rios et al., ; Rodgers and Thorson, ; Zoch and Turk, ). Some studies examined the entire newspaper (Davis, ; Gallagher, ; Len‐Rios et al., ), while others focused on the newspapers’ front pages (Gibbons, ; Potter, ; Zoch and Turk, ), news photographs (Blackwood, ; Miller, ; Rodgers and Thorson, ), the business section (Greenwald, ), or the sports section (Duncan, Messner, and Williams, ; Huggins, ). The findings of these studies are remarkably similar: they all reported substantial underrepresentation of female subjects.…”
Section: Females’ Newspaper Coverage: a Persistent Sex Gapmentioning
confidence: 99%
“…Over the last few decades, women's representation in the media has been examined by a myriad of studies. Alongside evidence for stereotypical and often sexualized and demeaning depictions (e.g., Fiske, ; Lester and Dente Ross, ; Tuchman, ; Van Zoonen, ), studies have also suggested that women are substantially underrepresented in the media in general and in the written press specifically (e.g., Davis, ; Duncan, Messner, and Williams, ; Greenwald, ; Potter, ; Zoch and Turk, ). Many have suggested that such “symbolic annihilation” (Tuchman, ) poses a serious problem for the way news media report on daily life and plays a significant role in maintaining the gendered balance of power (De Swert and Hooghe, ).…”
mentioning
confidence: 99%
“…Many studies have found that women are underrepresented in news stories (Rodgers & Thorson, 2003;Rodgers, Thorson, & Antecol, 2001), front pages (Gibbons, 2000;Potter, 1985), the New York Times Magazine ("Marginalizing," 1996;Zoch & Turk, 1998), business sections (Davis, 1982;Greenwald, 1990), and news photographs (Blackwood, 1983;Miller, 1975;Rodgers & Thorson, 2000). In fact, Potter's study of newspapers from 1913Potter's study of newspapers from , 1933Potter's study of newspapers from , 1963Potter's study of newspapers from , and 1983 found that the proportion of women portrayed decreased over time.…”
Section: Literature Reviewmentioning
confidence: 99%